Value Chain Analysis and Markets for Crop and Livestock Enterprises in the Cereal-Based Systems in the Ethiopian Highlands: Building Partnerships for Impact through Research on Sustainable Intensification of Farming Systems - International Livestock Research Institute (International Livestock Research Institute, 2014)
Determining the value chain actors and processes for the supply of inputs/services and the processing and marketing of selected marketable livestock and crop commodities. Determining the main channels used for processing and marketing of the produce by farmers. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/value_chain_analysis_eth